Uretrocystography Radiography with Urethra Stricture Study at the Adam Malik Hajj Center General Hospital Medan - Tambunan, Justinus; Nuryatno, Nudyatno (PT Inovasi Pratama Internasional, 2023)
Urethral stricture is a narrowing of the urethra caused by scar tissue ( fibrosis) which leads to obstruction of the urinary tract with potentially serious consequences for the urinary tract. Urethral stricture can cause symptoms of urinary obstruction and irritation that ultimately damage the kidneys. In this writing, the projections used are Anteroposterior (AP) and Right Posterior Oblique (RPO). This research was conducted at RSU Haji Adam Malik Medan in April – July 2021. The type of research used was descriptive qualitative research. Descriptive research is a search for facts with appropriate interpretation . The results of diagnostic examinations provide information about abnormalities in the urinary tract using Digital Radiography (DR) as film processing and Uretrocystography with suspected urethral stricture using a General x-ray unit with a capacity of 300 mA.